Pendampingan Pastoral Kedukaan: Implementasi Terhadap Jemaat yang Berduka Akibat Kematian di GKPPD Lae Salak. - Pebrien Kabeakan; Reymond P. Sianturi; Bernhardt Siburian; Erman Saragih; Bestian Simangunsong (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2024)
The purpose of this study was to analyze and evaluate the implementation of pastoral care in the church for congregations grieving due to death, and to understand the extent to which the congregation's understanding of the religious concept of death influences the way pastoral care is implemented and its impact on the grieving process. The research method used was descriptive qualitative, with data collection techniques through interviews, observations, and documentation studies. This study also aims to identify practical challenges faced in the implementation of pastoral care, especially in situations of sudden or complex death. The results of the study indicate that pastoral care in GKPPD Lae Salak needs to be improved in terms of the skills and knowledge of pastoral care workers in order to provide more effective support. This study provides benefits by providing input for the church to improve its pastoral care strategy.